Food scientist’s guide to fats and oils for margarine and spreads development - Morlok, Kathleen M. (Kansas State University, 2010)
Fats and oils are an important topic in the margarine and spreads industry. The selection of these ingredients can be based on many factors including flavor, functionality, cost, and health aspects. In general, fat is an important component of a healthy diet. Fat or oil provides nine calories per gram of energy, transports essential vitamins, and is necessary in cellular structure. Major shifts in consumption of fats and oils through history have been driven by consumer demand. An example is the decline in animal fat consumption due to consumers’ concern over saturated fats. Also, consumers’ concern over the obesity epidemic and coronary heart disease has driven demand for new, lower calorie, nutrient-rich spreads products. Fats and oils can be separated into many different subgroups. “Fats” generally refer to lipids that are solid at room temperature while “oils” refer to those that are liquid. Fatty acids can be either saturated or unsaturated. If they are unsaturated, they can be either mono-, di-, or poly-unsaturated. Also, unsaturated bonds can be in the cis or trans conformation. A triglyceride, which is three fatty acids esterified to a glycerol backbone, can have any combination of saturated and unsaturated fatty acids. Triglycerides are the primary components of animal and vegetable fats and oils. The ratio of saturated to unsaturated fatty acids in these fats and oils has a great impact on their functionality. Common fats and oils include butterfat, beef tallow, fish oils, soybean oil, rapeseed (canola) oil, corn oil, cottonseed oil, olive oil, sunflower oil, palm oil, palm kernel oil, coconut oil, linseed (flax) oil, and safflower oil. Typical fat and oil modification techniques include hydrogenation, interesterification, alternative hydrogenation, fractionation, blending, farm/field practices and genetic modification, and the use of fat replacers. There are many processing techniques that can be utilized in margarine and spreads production. The process can be optimized for each margarine or spreads product. There are many fats and oils in margarine and spreads formulations. Familiarity with commonly used fats and oils in regards to availability, cost, nutrition, chemistry, and functionality are important when creating a cost-effective, functional margarine or spreads product.
Keywords: Fats; Oils; Butter; Spreads; Margarine; Agriculture, Food Science and Technology (0359)